Florida's Citrus Canker Eradication Program (CCEP): Annual Economic Impact on Florida's Specialty Citrus Fruit Market - Thomas H. Spreen; Marisa L. Zansler; Ronald P. Muraro (EDIS)
In the analysis presented in this paper, the benefits of the Citrus Canker Eradication Program (CCEP) on Florida's specialty citrus fruit industry are estimated through an analysis of the Florida citrus industry under the scenario that citrus canker has become established, holding all other factors constant. The net change in revenue in the fresh and processed markets and the additional costs of production were the measurements of the estimated benefits. This is EDIS document FE535, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published August 2005.